2003
DOI: 10.1002/art.10879
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of systemic lupus erythematosus–associated type B insulin resistance syndrome with cyclophosphamide and mycophenolate mofetil

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by loss of immunologic self-tolerance and the subsequent development of autoantibodies. These antibodies are thought to be important in relation to the clinical manifestations of the disease. One example is the development of multiple cytopenias secondary to cytolytic or cytotoxic antibodies directed toward red blood cells, platelets, and white blood cells. Other antibodies may mediate abnormal cellular mechanisms such as those seen with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…TNF-α and IL-6 however was increased in our SLE patients with renal involvement, but this increase was not statistically significant. The borderline elevation of these cytokines was probably due to administration of immunosuppressive drugs to our patients which has also been reported by Gehi et al [53]. …”
Section: Discussionsupporting
confidence: 58%
“…TNF-α and IL-6 however was increased in our SLE patients with renal involvement, but this increase was not statistically significant. The borderline elevation of these cytokines was probably due to administration of immunosuppressive drugs to our patients which has also been reported by Gehi et al [53]. …”
Section: Discussionsupporting
confidence: 58%
“…Systemic inflammation and anti-insulin antibodies could promote the development of insulin resistance (38,39), with the ensuing dyslipidemia, hypertension, and increase in body weight. Also, endothelial damage and dysfunction, induced by lupus systemic inflammation, can be accompanied by overproduction of the vasoconstrictors thromboxane and endothelin 1, leading to elevation of BP (40).…”
Section: Discussionmentioning
confidence: 99%
“…In rare clinical cases, patients with SLE develop antibodies to the insulin receptor, which cause insulin resistance (type B insulin resistance). 19 Independent of these case studies, currently available data suggest that humans with SLE are at an increased risk to develop insulin resistance and obesity. For example, it has been reported that individuals with SLE have significantly increased body mass index at a 10-year follow-up compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%